Country Insurance : The Role of Domestic Policies. (Policy Papers; Policy Paper ;, 2006)
Member countries are routinely faced with a range of shocks that can contribute to higher volatility in aggregate output and, in extreme cases, to economic crises. The presence of such risks underlies a potential demand for mechanisms to soften the blow from adverse economic shocks -- 'country insurance' for short. Protective measures that countries can take themselves ('self-insurance') include sound economic policies, robust financial structures, and adequate reserve coverage. Beyond self insurance, countries have also established regional arrangements that pool risks, while at the multilateral level the IMF has a central role in making its resources temporarily available to attenuate the costs of economic adjustment when shocks create balance of payments difficulties for a member. This paper analyzes a number of mechanisms through which countries can self-insure, leaving the role of collective regional and multilateral arrangements to subsequent papers.